Living life to the fullest : disability, youth and voice - Liddiard, Kirsty; Whitney-Mitchell, Sally; Evans, Katy; Watts, Lucy; Spurr, Ruth; Vogelmann, Emma; Runswick-Cole, Katherine; Goodley, Dan (Emerald Publishing Limited, 2022)
This co-authored text critically explores the key findings of the Living Life to the Fullest project - a project that has explored the lives, thoughts, hopes and aspirations of disabled young people living with life-limiting and life-threatening conditions. Written by disabled young people and academic researchers, the book articulates ethical co-production in social research. The prolific contemporary political and theoretical debates about life, death and the human in an age of global precarity and austerity are explored in this book. Chapters draw upon key themes and co-researchers' priorities for writing about their lives: for example, the politics and potentials of co-production as a research method/ology; animal and human relationships; aging, time; sexuality and body image; politics, activism and disability arts and culture; and fragility, and death and dying.
Keywords: Youth with disabilities.; Social Science, People with Disabilities.; Coping with disability.; elektronické knihy; electronic books